Antibacterial activity of Fe2O3/MgO Nanoparticles against Escherichia coli isolated from contaminated Water: Aktivitas Antibakteri Nanopartikel Fe2O3/MgO terhadap Escherichia coli yang diisolasi dari Air yang terkontaminasi - Ali A. Fayyadh; Jawad N. K. Makassees; Ali K. Hattab (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Water contamination by pathogenic bacteria, particularly Escherichia coli, poses serious public health risks, necessitating the development of effective antibacterial agents. Specific Background: Nanoparticles synthesized via green chemistry offer an environmentally sustainable alternative for bacterial control, with metal oxide nanoparticles demonstrating promising antimicrobial properties. Knowledge Gap: Despite extensive research on metal oxide nanoparticles, comparative studies on Fe₂O₃ and MgO nanoparticles synthesized from Allium sativum extract remain limited, particularly regarding their antibacterial efficacy against E. coli in contaminated water. Aims: This study investigates the antibacterial activity and characterization of Fe₂O₃ and MgO nanoparticles synthesized via a green synthesis method using Allium sativum extract, evaluating their efficacy against E. coli isolates. Results: Characterization via X-ray Diffraction (XRD), Transmission Electron Microscopy (TEM), and Fourier Transform Infrared Spectroscopy (FTIR) confirmed the structural and morphological properties of the nanoparticles. Fe₂O₃ nanoparticles exhibited superior antibacterial activity, generating 20 mm inhibition zones compared to MgO's 12-15 mm zones, attributed to their smaller size (24.41 nm), amorphous nature, and increased surface area. Novelty: This study highlights the potential of Allium sativum-mediated Fe₂O₃ nanoparticles as a more effective antibacterial agent than MgO nanoparticles. Implications: These findings support the application of green-synthesized metal oxide nanoparticles in sustainable water treatment solutions, contributing to advancements in antimicrobial technology. Highlights: Higher Antibacterial Efficiency – Fe₂O₃ outperforms MgO in inhibition zones. Eco-Friendly Synthesis – Allium sativum ensures green nanoparticle production. Water Treatment Potential – Effective against bacterial contamination in water. Keywords: Fe₂O₃ nanoparticles, MgO nanoparticles, antibacterial activity, green synthesis, water treatment